Attitudes of researchers in educational institutions towards the use of the Internet in scientific research (Journal of the College of Basic Education, 2022)
The use of the Internet and benefiting from it in scientific research by researchers in institutes and universities has become one of the essential things to keep abreast of scientific developments, and this requires the institutes to provide the appropriate environment for them, so the study sought to identify the problems and difficulties that they face when using the Internet in addition to knowing the reasons for using the Internet in Scientific Research .